Antiepileptic drugs - Levy, René H; Mattson, Richard H; Meldrum, Brian S (Raven Press, 1995)
Here is the latest edition of the classic reference for clinicians and researchers in epileptology and neurology. Encyclopedic in scope, the Fourth Edition is completely revised, updated, and expanded to provide the most authoritative information currently available on the mechanisms of action; chemistry and biotransformation; absorption, distribution, and excretion; interactions; clinical use; and toxicity of the antiepileptic drugs currently in use or undergoing research. Coverage begins with a thorough grounding in general principles, including pharmacokinetics, mechanisms of action and toxicology, and selection and use of drugs for specific patient populations. The book then explores specific drugs, including phenytoin, phenobarbital and other barbiturates, primidone, carbamazepine, valproic acid, ethosuximide, oxazolidinedione, and benzodiazepines. Complete information is provided on recently approved antiepileptic drugs: felbamate, gabapentin, lamotrigine, oxcarbazepine, and vigabatrin. The book also examines a wide variety of other antiepileptic drugs and five potential anticonvulsant drugs currently undergoing investigation.
Keywords: Epilepsy; epilepsie; neurovědy; farmacie a farmakologie; antikonvulziva; Anticonvulsants